LATE CENOZOIC ACTIVE FOLD-AND-THRUST BELTS IN THE SOUTHERN AND NORTHERN FLANKS OF TIANSHAN - Guan S.; Li B.; He D.; Wang X.; Suppe J.; Lei G. (My University, 2007)
The Tianshan Mountain range related to the India-Eurasia collision has been considered as an ideal laboratory to understand the dynamic processes responsible for intracontinental mountain building. The active fold-and-thrust belts in its both flanks offer an exceptional opportunity to study the processes of growth folding above imbricate thrust systems and their interaction with sedimentation and displacement, which are emphasized more and more by the worldwide neotectonic community. In order to present a detailed and quantitative analysis of the timing, rates and process of deformation on these active fold-and-thrust belts, depth-converted seismic reflection profiles, wells, together with detailed surface structural measurements, have been used to construct balanced cross-sections in the Kuqa river and Jingou-Anjihai river areas, located in the southern and northern piedmonts of Tianshan respectively. Growth strata and growth unconformities analysis correlated to the available magnetostratigraphy indicates actively deforming structures in both areas may have mainly developed since the early Pliocene (4.2-5 Ma). In Kuqa river cross-section, the displacements on three thrust faults, estimated by geometric analysis, vary from 5.7 km to 6.3 km, and to 18 km, which reveals an acceleration of deformation since the Oligocene. Based on these measurements, we infer a long-term (23Ma) shortening rate of the Kuqa thrust-and-fold belt of about 1.3 mm/a, and the short-term (4.2-5 Ma) shortening rate of about 3.6 mm/a. In the Jingou-Anjihai river cross-section, the total displacement on thrust faults in deep wedges near the mountain front is estimated to be about 16.9 km, in which only 6 km is transferred to the Huo'erguoshi anticline, and has decreased to 0.22-0.28 km near the Anjihai anticline. Based on these measurements, we infer the shortening rate of the upper and lower structural layers of about 2.6-3.1 mm/a and 3.8-4. 5 mm/a, respectively, and the deep structural wedges near the mountain front, Huo'erguoshi deep anticline and Anjihai anticline in the lower structural layer of about 3.9-4.6 mm/ a, 1.2-1.4 mm/a and 0.04-0.38 mm/a, respectively.
Keywords: DISPLACEMENT; JINGOUHE-ANJIHAIHE CROSS-SECTION; KUQA CROSS-SECTION; PLIOCENE; SHORTENING RATE; STRUCTURAL DEFORMATION; TIANSHAN; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен